Small range distributions in the high Andes: two new species of Liaghinella (Hemiptera: Heteroptera: Reduviidae: Emesinae) from Colombia - Castro-Huertas, Valentina; Forero, Dimitri (Zootaxa, 2017)
Liaghinella Wygodzinsky, 1966 (Hemiptera: Heteroptera: Reduviidae: Emesinae: Metapterini), is an endemic Neotropical genus with two described species, one from Jamaica and one from Colombia. In this paper we describe two additional new species from the high Andes in Colombia, Liaghinella heldamariae sp. nov from Monserrate and Villa de Leyva, and L. tuberculata sp. nov. from Chicaque Natural Park, both in the Eastern Cordillera. The new species were collected very close to the type locality of the previously known Colombian species, L. andina Forero, 2007. These two new species differ from L. andina by having both a pair of conspicuous tubercles on the posterior margin of the pronotum, and by the structure of the male and female genitalia. Species diagnosis and descriptions, digital macrophotographies, and a key to separate the species of Liaghinella are presented. A discussion on the small range distributions exhibited by the high Andean species of Liaghinella is provided.